Public Utility Holding Companies. hearings before the United States House Committee on Interstate and Foreign Commerce, Seventy-Fourth Congress, first session, on Apr. 5, 9-12, 15, 1935. (U.S. Congressional Hearings., 1935)
Considers (74) H.R. 5423.